COVID-19: Remote diagnostic assessment of children with suspected Autism Spectrum Disorder, a selected literature review - Carrieri, Liliana; Bentenuto, Arianna; Venuti, Paola; Bertamini, Giulio; de Falco, Simona (Rivista di Psicologia Clinica - Open Access, 2024)
Diagnostic evaluations of neurodevelopmental disorders dramatically reduced and slowed down following the disruptions caused by Sars-CoV-2 pandemic. For this, it was necessary to identify solutions allowing diagnostic assessment, screening, and early patient care by implementing remote diagnostic protocols respecting the restrictions imposed by the lockdown. Centres and services specialized in Autism Spectrum Disorder (ASD) had to quickly implement innovative diagnostic protocols able to satisfy patients’ needs, minimizing the chances of spreading the virus at the same time. This work collects the studies conducted so far on remote assessment of ASD both prior to and relating to the period of the SARS-CoV-2 pandemic. It also explores standard diagnostic tools that have been adapted for remote administration, in order to evaluate strengths and limitations of these methodologies. Remote assessment methodologies were initially employed to overcome the difficulties of long-distance diagnoses and to respond to families’ need for continuity of public and private services. These studies underlined the validity of some remote diagnostic protocols and how telediagnosis may enable the diagnostic evaluation, making it more accessible and thus favouring timely intervention. We discussed the opportunity to integrate in person and remote approaches for diagnosing neurodevelopmental conditions, even in the post covid emergency period.